Traian Vuia şi regimul democrat-popular din România - Pavel Ţugui (Revista de Istorie și Teorie Literară)
Known as a great inventor and pilot, Traian Vuia is now revealed as a great patriot as well. He got involved in politics of the First World War and empathized with the Romanian people during that period; he also fought for the rights of the Romanians in Bucovina and Transylvania. The article contains, besides dates and events in Vuia’s life, a series of letters and notes written by Petru Groza and Pavel Țugui concerning the life of the inventor.